Management of Pulp and Paper Mill Waste - Bajpai, Pratima (Springer International Publishing : Imprint: Springer, 2015)
Pulp and paper mill industries are always associated with the disposal problem of highly contaminated sludge or bio-solids. The development of innovative systems to maximize recovery of useful materials and/or energy in a sustainable way has become necessary. The management of wastes, in particular of industrial waste, in an economically and environmentally acceptable manner is one of the most critical issues facing modern industry, mainly due to the increased difficulties in properly locating disposal works and complying with even more stringent environmental quality requirements imposed by legislation. This book presents a general Introduction on waste management in the pulp and paper industry and contains topics on the generation of waste in pulp and paper mills, waste composition, methods of sludge pre-treatment, processes and technologies for conversion of pulp and paper mill waste into valuable products, waste reduction techniques employed in the pulp and paper Industry worldwide and future trends.